Quality of spray dried soy beverage powder as affected by drying and feed parameters. Issue 4 (10th July 2017) - Giri, Saroj Kumar; Mangaraj, Shukadev; Sinha, Lalan Kumar; Tripathi, Manoj Kumar
Abstract : Purpose: Soy beverage is becoming more and more popular because it is touted as a healthy food containing useful phytochemicals and is free from lactose and cholesterol. The purpose of this paper is to optimize the spray drying process parameters for obtaining soy beverage powder with good reconstitution and handling properties. Design/methodology/approach: Pre-concentrated soy beverage was dried in a laboratory model spray dryer, and the effects of inlet air temperature (180-220°C), feed rate (20-40 ml/min) and feed solid content (15-25 per cent) on some physical parameters and reconstitution properties (wettability and dispersibility) of spray-dried soy beverage powders were investigated. Second order polynomial response surface model was selected for the analysis of data and optimization of the process. Findings: Spray drying of soy beverage at different processing conditions resulted in powders with particle size (volume mean diameter) in the range of 86 to 156 µm. Dispersibility and wetting time of the spray-dried soy beverage powders was found to be in the range of 56 to 78 per cent and 30 to 90 s respectively, under various drying conditions. Inlet air temperature was found to be the main factor affecting most of the quality parameters, followed by solid content of the feed. Temperature significantly affected the wettability, dispersibility, colour parameters, particle size and flowability of the powder at p ≤ 0.01. Lower temperature and higher feed solid content produced bigger-sized powder particles with better handling properties in terms of flowability and cohesiveness. A moderate inlet air temperature (196°C), higher feed solid content (24 per cent) and lower feed rate (27 ml/min) were found suitable for drying of soy beverage. Practical implications: The study implied the possibility of producing powder from soy beverage using the spray-drying method and optimized drying conditions for obtaining soy beverage powder with good reconstitution properties. Originality/value: The finding of this study demonstrated for the first time how the inlet air temperature, feed solid content and feed rate during spray-drying influenced different quality parameters of soy beverage powder. Further, an optimized drying condition has been identified.